2006
DOI: 10.2320/matertrans.47.1247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interfacial Thermal Resistance on Effective Thermal Conductivity of MoSi<SUB>2</SUB>/SiC Composites

Abstract: The thermal conductivity of molybdenum disilicide composites reinforced with 100 nm and 0.5 mm silicon carbide particles was determined as the function of volume fraction of silicon carbide. Due to interface effect, the thermal conductivity of composites with same volume fraction of silicon carbide decreased with decreasing inclusion size. It has been found that at lower inclusion content, interfacial thermal resistance dominates in determining composite thermal conductivity, while with increasing content of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For a low volume content of w ‐BN below 20 vol %, λ th exhibits an untypical decrease from 0.21 to 0.12 W/mK which are values below those of neat PI. Other authors have already observed such behavior in other nanocomposite materials . For a higher volume content of w ‐BN beyond 20 vol %, λ th increases up to 0.25 W/mK for 57.2 vol %.…”
Section: Resultsmentioning
confidence: 56%
“…For a low volume content of w ‐BN below 20 vol %, λ th exhibits an untypical decrease from 0.21 to 0.12 W/mK which are values below those of neat PI. Other authors have already observed such behavior in other nanocomposite materials . For a higher volume content of w ‐BN beyond 20 vol %, λ th increases up to 0.25 W/mK for 57.2 vol %.…”
Section: Resultsmentioning
confidence: 56%
“…In addition, interfacial imperfections, induced by the mismatch of the thermal expansion coefficient between alumina and SiC nanoparticles, also affect the thermal conductivity of the composites. 48 In our study, the high aspect ratio of MWNTs and probably the enhanced connectivity achieved in a hybrid filler have reduced this value to only 3 vol% for the alumina matrix. 46,47 The decrease in the thermal conductivity of the composites by addition of SiC due to interface thermal resistance has also been reported earlier.…”
Section: Wwwceramicsorg/actmentioning
confidence: 57%
“…Thus lowering the interface density or in turn interface resistance that may result in increase of thermal conductivity as reported for 30 vol% SiC/MoSi 2 composites. 48 In our study, the high aspect ratio of MWNTs and probably the enhanced connectivity achieved in a hybrid filler have reduced this value to only 3 vol% for the alumina matrix. Because of the intragranular fracture mode of the hybrid nanocomposites, it is somewhat difficult to show the hybrid percolation network at the grain boundaries.…”
Section: Wwwceramicsorg/actmentioning
confidence: 57%
See 1 more Smart Citation
“…High quality joints of this type are obtained by careful surface preparation and application of advanced manufacturing techniques, like chemical or physical vapour deposition [4,5]. To characterize the heat transfer through the boundary between solids remaining in direct contact the notion of interfacial thermal resistance (ITR) is utilized [3,6]. Apart from thermal contact resistance related to poor mechanical and chemical bonding it includes thermal boundary resistance (TBR) influence which results from the differences in conductive characteristics of contacting media such as velocities and densities of heat carriers [1,6,7].…”
Section: Introductionmentioning
confidence: 99%